Combinatorial on-chip study of miniaturized 3D porous scaffolds using a patterned superhydrophobic platform - Oliveira, Mariana B. (2013)
One of the main challenges in tissue engineering (TE) is to obtain optimized products, combining biomaterials, cells and soluble factors able to stimulate tissue regeneration. Multiple combinations may be considered by changing the conditions among these three factors. The unpredictable response of each combination requires time-consuming tests. High-throughput methodologies have been proposed to master such complex analyses in TE. Usually, these tests are performed using cells cultured into 2D biomaterials or by dispensing arrays of cell-loaded hydrogels. For the fi rst time an on-chip combinatorial study of 3D miniaturized porous scaffolds is proposed, using a patterned bioinspired superhydrophobic platform. Arrays of biomaterials are dispensed and processed in situ as porous scaffolds with distinct composition, surface characteristics, porosity/pore size, and mechanical properties. On-chip porosity, pore size, and mechanical properties of scaffolds based on chitosan and alginate are assessed by adapting microcomputed tomography equipment and a dynamic mechanical analyzer, as well as cell response after 24 hours. The interactions between cell types of two distinct origins—osteoblast-like and fi broblasts—and the scaffolds modifi ed with fi bronectin are studied and validated by comparison with conventional destructive methods (dsDNA quantifi cation and MTS tests). Physical and biological on-chip analyses are coherent with the conventional measures, and conclusions about the most favorable conditions for each cell type are taken.